Phase-dependent iron depletion differentially regulates the niche of intestinal stem cells in experimental colitis via ERK/STAT3 signaling pathway - Wang, Shubin; Liu, Xiangjun; Xu, Lu; Lang, Jinyi; Liu, Dengqun (Frontiers in Immunology, 2025)
IntroductionUlcerative colitis (UC) is a global gastrointestinal disease, which is mainly caused by both dysfunctional epithelial barrier and inflammation response. Iron is a critical fundamental element for both the maintenance of homeostasis and the mediation of inflammation in many tissues. However, the role and mechanism of iron in the phase of enteritis and the subsequent repairing phase of intestinal stem cells has not been elucidated. In this study, we aimed to explore whether and how iron depletion would affect the occurrence and outcome of experimental colitis.MethodsIron depletion was realized by deferoxamine (DFO) at either the early stage or late stage of dextran sulfate sodium (DSS) induced experimental colitis in mice. The gross images of colons, general health, histology, barrier integrity, and qRT-PCR were performed. Meanwhile, cell culture and colonic organoids were used to examine the influence of iron depletion in vitro. Signaling pathway and inflammatory infiltration were investigated by immunostaining.ResultsIron depletion within the early stage of DSS treatment significantly inhibited the onset of the inflammatory response, maintained the integrity of the colonic epithelium, and preserved the activity of intestinal stem cells (ISCs) both in vivo and in vitro. However, both continuous iron depletion by DFO and late DFO treatment aggravated colonic injury and postponed the recovery from colitis. Early DFO-induced iron depletion was able to maintain the p-STAT3 and p-ERK1/2 signaling pathways within the colonic epithelium at the early phase of colitis, but late DFO treatment inhibited the activity of these two pathways.DiscussionOur study demonstrated that the manipulation of iron depletion by DFO might greatly affect the outcomes of experimental colitis in a phase-dependent manner, which suggests that the balance of iron metabolism might be an effective therapeutic target for the clinical treatment of IBD patients.